Development of IPA Learning Module Using STEMK WASAKA Learning Model to Improve Learning Outcomes - Rabiatul Adawiyah; Syubhan Annur; Mella Mutika Sari (Jurnal Pijar MIPA, 2026)
The way students learn science at SMP Negeri 1 Tabunganen is mostly through lectures and is teacher-focused, which leads to poor learning results, students not being actively involved, and trouble understanding the human digestive system. Because of this, researchers decided to create a science learning module using the STEMK WASAKA model, which emphasises responsibility, discipline, and cooperation. The study aims to check if this module is valid, practical, and effective for teaching the human digestive system. The method used was Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The students involved were from the eighth grade at SMP Negeri 1 Tabunganen. Data was collected using expert validation sheets, student feedback questionnaires, and pretests and posttests. The results showed that the module had moderate validity (average score of 0. 758), high reliability (α = 0. 745), very high practicality (86. 91%), and sufficient effectiveness with an N-gain value of 0. 65. Therefore, the STEMK WASAKA-based science learning module is considered valid, practical, and effective enough to help improve student understanding of the human digestive system.